2019
DOI: 10.1520/jte20180025
|View full text |Cite
|
Sign up to set email alerts
|

Remote Measurements and Vibration Analysis of Existing Wind Turbines

Abstract: Extreme weather is a constant threat to the service of a wind turbine, as it may cause damage to the rotor blades or even lead to the collapse of a supporting tower. A change in the dominant frequency may indicate a deviation from the design of the stiffness of the turbine-tower system. Dynamic measurements of the lateral displacement of four 2-MW wind turbines of the same model have been obtained using a ground-based microwave interferometer. Vibration analysis, including frequency domain decomposition and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Currently, this technology still remains immature for its practical implementation in gas turbines. Other recent studies reported new contactless vibration measurement systems based on laser scanning and ground-based radars [31][32][33], but they can only be used for detecting large vibration amplitudes in operating blades. The recent development of MEMS-based fabrication techniques has provided an alternative for designers owing to their cost-effective and lightweight features that make them particularly attractive for the vibration monitoring in rotating structures.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, this technology still remains immature for its practical implementation in gas turbines. Other recent studies reported new contactless vibration measurement systems based on laser scanning and ground-based radars [31][32][33], but they can only be used for detecting large vibration amplitudes in operating blades. The recent development of MEMS-based fabrication techniques has provided an alternative for designers owing to their cost-effective and lightweight features that make them particularly attractive for the vibration monitoring in rotating structures.…”
Section: Introductionmentioning
confidence: 99%
“…As a clean, safe, and sustainable natural source, wind energy becomes increasingly important in power supply [1][2][3]. Plenty of new wind farms have been installed in mountainous and hilly regions in many countries as a strategy for narrowing the regional energy disparity [4,5].…”
Section: Introductionmentioning
confidence: 99%